What do we learn from ratings about corporate social responsibility? New evidence of uninformative ratings - Yang, Ruoke (Journal of Financial Intermediation, 2022)
The rise of investments professionally managed with a socially responsible mandate has generated growing interest in environmental and social ratings. However, it is not clear how informative these ratings are or whether they are distorted by greenwashing. Based on the ratings of the leading provider, I offer the first evidence linking greenwashing to ratings inflation. Better ratings do not predict less future corporate bad behavior. This is of concern because it undermines the signaling value of these ratings. To understand these results, I develop a model where the rating agency may underinvest in greenwashing detection while firms have incentives to window dress and engage in greenwashing. Finally, controlling for greenwashing improves ratings predictive quality.